Avengers citizen kang ebook - Thomas, Roy (Avengers: Citizen Kang., 2015)
Collects Captain America Annual #11, Thor Annual #17, Fantastic Four Annual #25 and Avengers Annual #21. In the unassuming town of Timely, Wisconsin, the Vision has disappeared, and it's up to the Fantastic Four and the Avengers to save him! But Timely is connected to Kang's city of Chronopolis, which spans the entire history of the Earth and is guarded by the deadliest warrior's of every age, the Anachronauts! Can the Avengers and the Fantastic Four stop battling each other long enough to defeat Kang and the conniving Terminatrix? Guest-starring Gilgamesh and Dr. Druid!